2005
DOI: 10.1158/0008-5472.can-04-4292
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HER-2/neu Kinase Impairs Androgen Receptor Recruitment to the Androgen Responsive Enhancer

Abstract: Advanced prostate cancer invariably recurs despite androgen deprivation therapy. The androgen receptor (AR) likely plays a key role in this progression and in the continued survival and proliferation of prostate cancer cells in the low androgen environment. Cross-talk with growth factor receptors, such as epidermal growth factor receptor (EGFR) family, has been postulated as a potential mechanism to activate AR in recurrent prostate cancer. We have investigated the role of HER-2/neu (ErbB-2) tyrosine kinase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 21 publications
6
65
0
Order By: Relevance
“…These results suggest that Ack1 is a critical intermediate of HER2 signaling in prostate cancer cells and its activation of ARregulated genes (13). The effect of Ack1 knockdown on androgen target gene expression such as PSA and hK2 and recruitment and DNA binding of AR is similar to the reported effect of HER2 inhibition or knockdown (14,15). Cells expressing activated Ack1 exhibit enhanced recruitment and DNA binding of AR and increased androgen target gene expression.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…These results suggest that Ack1 is a critical intermediate of HER2 signaling in prostate cancer cells and its activation of ARregulated genes (13). The effect of Ack1 knockdown on androgen target gene expression such as PSA and hK2 and recruitment and DNA binding of AR is similar to the reported effect of HER2 inhibition or knockdown (14,15). Cells expressing activated Ack1 exhibit enhanced recruitment and DNA binding of AR and increased androgen target gene expression.…”
Section: Discussionsupporting
confidence: 65%
“…We and others have demonstrated that heregulin-dependent HER2/HER3 receptor tyrosine kinase signaling enhances AR activity (12)(13)(14)(15); the effect of activated Ack1 on AR-dependent gene expression was similar to that which we observed by heregulin-dependent activation of the HER2/HER3 heterodimer (13). Therefore, we tested whether Ack1 may act as a downstream mediator of HER2/ HER3 on AR.…”
Section: Heregulin-mediated Her2 Tyrosine Kinase Activation Leads To supporting
confidence: 64%
See 3 more Smart Citations